Time and family on the move: 'Accompanying partners' in geographical mobility. (4th February 2020) - Suter, Brigitte; Cangià, Flavia
Under conditions of global economy, geographical mobility becomes an important aspect of the working lives for a wider range of professionals. At times, these people move with their families. The relocation to a new country can entail changes for the whole family, in particular for the partner, who can experience a more pronounced alteration of work–family relations. Especially for dual career couples, with both partners employed before migration, the change in the experience of time can be very profound for the accompanying partner who can move from being a full-time professional to being a full-time homemaker. Based on two studies conducted respectively in China and Switzerland with mobile families, we explore how accompanying partners experience and practice time in the context of migration with the family. We discuss how, while time for the contracted partner can still be structured by work, a more ambivalent mixture of personal desire, family relations, cultural values and social expectations seem to affect the subjective experience of time for the accompanying partner.